One Economics, Many Recipes: Globalization, Institution, and Economic Growth. - ศิริประชัย สมบูรณ์ (Journal of Business, Innovation and Sustainability (JBIS), 2009)
Download files DOI: http://dx.doi.org/10.14456/becj.2009.11